Essential newborn care practice and its associated factors in Southwest Ethiopia - Haimanot Abebe; Daniel Adane; Solomon Shitu (BMC, 2021)
Abstract Background Essential newborn care is a wide-ranging strategy intended to improve the health of newborns by implementing appropriate interventions. Approximately in 2018, an estimated 2.5 million children died in their first month of life, which is approximately 7000, newborns every day, with about a third of all neonatal deaths occurring within the first day after birth. Even though the most cause of death is preventable the burden of neonatal death is a still high in developing countries including Ethiopia. Therefore this study is aimed to assess the level of essential newborn care practice among mothers who gave birth within the past six months in Gurage Zone, Southwest Ethiopia. Methods A community-based cross-sectional study was conducted among mothers who gave birth within the past six months in Gurage Zone, Southwest Ethiopia. For the quantitative part, 624 study participants were involved by using a multi-stage sampling method. A systematic random sampling technique was to reach the study subjects. Data entry was carried out by Epi data version 4.0.0 and analysis was done by SPSS window version 24. Binary and multivariate logistic regressions were used to identify associated factors. For the qualitative part, three focus group discussions (FGD) with purposively selected 30 mothers were involved. The data were analyzed deductively by using the thematic framework analysis approach by using Open code version 4.02. Result Overall good essential newborn care practice was found to be 41.0% [95%CI, 36.6-44.7]. Being urban residence [AOR 1.70, 95%CI: 1.03-2.79], attending antenatal care visit [AOR = 3.53, 95%CI: 2.14-5.83], attending pregnant mothers meeting [AOR = 1.86, 95%CI: 1.21-2.86], had immediate postnatal care [AOR = 3.92, 95% CI: 2.65-5.78], and having good knowledge about ENC [AOR = 2.13, 95% CI: 1.47-3.10] were significantly associated with good essential newborn care practice. Conclusion This study indicated that the magnitude of essential newborn care practice was low. Thus, a primary health care provider should regularly provide ENC for newborns and take opportunities to counsel the mothers about ENC during pregnant mothers meeting and MCH services sessions.